1993
DOI: 10.1002/chin.199346335
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Catechins of Green Tea: Antioxidant Activity

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…(1983) pointed out that EC exhibited better antioxidant activity than other catechins. Lunder (1992) found that the EGCG content of tea leaves correlated well with its antioxidant activity. Chen and Ho (1995) studied antioxidant activities by the Rancimat method and the effectiveness in the inhibition of lipid peroxidation was in the descending order: EGCG > ECG > EGC > EC.…”
Section: Resultsmentioning
confidence: 99%
“…(1983) pointed out that EC exhibited better antioxidant activity than other catechins. Lunder (1992) found that the EGCG content of tea leaves correlated well with its antioxidant activity. Chen and Ho (1995) studied antioxidant activities by the Rancimat method and the effectiveness in the inhibition of lipid peroxidation was in the descending order: EGCG > ECG > EGC > EC.…”
Section: Resultsmentioning
confidence: 99%
“…Green tea ( Camellia sinensis ), one of the most common beverages in the world, is usually brewed in cold or hot water. The beverage has been claimed to have an array of health benefits including anticancer and antioxidant abilities [1] [2] . The agents responsible for health improvement from tea are known as catechins.…”
Section: Introductionmentioning
confidence: 99%
“…There are four major types of catechins in tea, epigallocatechin-3-gallate (EGCG), gallocatechin gallate (GCG) epigallocatechin (EGC), epicatechin gallate (ECG), and epicatechin (EC), with EGCG being the most abundant among all catechin types [3] . As EGCG contains eight hydroxyl (OH - ) groups, it can remove multiple free radicals which allows it to become one of the more potent antioxidants [3] [2] , additional researches show that the chemical has anti-cancer [1] , anti-inflammatory effects and can improve learning and memory retention skills [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The composition of black tea leaf is shown in Table 1. The literature reports a wide range of polyphenol compositions, from 8–40% (Balentine 1992; Lunder 1992; Astill et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of black tea leaf is shown in Table 1. The literature reports a wide range of polyphenol compositions, from 8-40% (Balentine 1992;Lunder 1992;Astill et al 2001). The polyphenols present in black tea are mainly TRs, TFs, bisflavanols, and catechins (Todisco et al 2002).…”
Section: Introductionmentioning
confidence: 99%